The university in the first battle line. Interview with Gustavo De la Rosa, (University of Ciudad Juarez, Mexico) - Miguel A. Zabalza Beraza; Laura Lodeiro Enjo (Universitat Politècnica de València, 2011)
Dr. Gustavo De la Rosa is a professor of Law at the Universidad Autónoma de Ciudad Juárez, México. He combines his work as a university teacher with the role of Chair of the Human Rights Commission of the State. In his long professional career he has gone through such significant positions as a student  leader, a labor lawyer, director of the prison in Ciudad Juarez and defender of human rights in a so complex city like Ciudad Juarez. This social engagement strongly affected his work as a university teacher, task that he has worked with intensity and commitment over the past 16years. His vision of the university and his way of approaching learning-as a service to the community offers a different perspective of the social commitment that the university should play in conflictive contexts.